Empowering Glamping Entrepreneurs through Financial and Marketing Training at Agro Puncak Bukit Lestari Tabanan - Adinegara, Gusti Ngurah Joko; Komalasari, Yeyen; Santoso, R. Tri Priyono Budi; Trimurti, Christimulia Purnama; Junaedi, I Wayan Ruspendi; Nainggolan, Gilbert (PT Agung Media Publisher, 2025)
Business sustainability requires not only the provision of products and facilities but also effective marketing activities and structured financial management. However, problem identification revealed that marketing practices in the glamping business remain conventional, relying solely on existing customers without targeting specific markets, while financial reporting is still unstructured. This community service program was conducted in three stages: preparation, implementation, and evaluation. The activities included training and mentoring on financial management, financial report preparation, and marketing strategies for glamping managers. The training improved participants’ ability to prepare financial reports, starting from recording transactions to producing structured financial statements. In addition, participants gained a better understanding of marketing program strategies, particularly in identifying and managing target markets. Evaluation results indicated an 89% increase in participants’ understanding of both financial management and marketing practices. The program contributed significantly to enhancing the managerial capacity of glamping businesses, particularly in marketing and financial management. These improvements are expected to support long-term business performance and sustainability.